Negotiation parameters of needs versus interest towards sustainability of halal talents in Malaysia - Abdul Rahim, Norhayati Rafida; Y, Noor Azrina; M, Siti Zubaidah; Awang, Muhammad Nizam; Ahmad Sabri, Safiyyah; Bolong, Jusang; Kamarulzaman, Nitty Hirawaty (Academic Inspired Network, 2020)
Malaysia is recognized as the Halal Hub in the region of Asia and a leader in the world’s Halal industry. As a progressive Muslim country with consistent economic development and growth rate as well as political and social stability. As announced by Malaysian Minister of International trade and Industry in 2017, one of the pertinent issues that must be addressed by the country if it wishes to achieve global halal hub status by 2020 is sustainability. In order to achieve the sustainability, the study wishes, 1) to identify the negotiation parameters of interest among halal talents in Malaysia; and 2) to identify the negotiation parameter of needs among halal talents in Malaysia. A qualitative approach is employed through a depth interview with five halal experts representing industries, authority, academicians and non-governmental organization (NGO). The findings reveal an emphasis on the parameter of needs have been negotiated more than the interests in halal sustainability framework for halal talents in Malaysia. It is suggested that the halal industries should give priorities to the needs of halal talents in terms of wages, promotion and trainings respectively.